A rare case of patellar fracture with quadriceps tendon rupture - Subramanian, K. N.; Ram, Ganesan G.; S., Muthukumar; Babu, Mathiyazhagan (International Journal of Research in Orthopaedics, 2021)
Quadriceps tendon rupture is the rarest injury with an incidence of 1.37/1,00,000/year. A patellar fracture is the most common injury associated with extensor mechanism lag, but it is rarely found to have quadriceps rupture rather than patellar tendon rupture. Normally when patella fracture occurs the force is disseminated at the bone level rather than at the muscular level. In this case, the force has disseminated at both muscle and bone leading to fracture of patella and quadriceps tendon rupture. Here we report a case of patellar fracture along with quadriceps tendon rupture.